Hands-On Music Generation with Magenta : Explore the Role of Deep Learning in Music Generation and Assisted Music Composition.: Explore the Role of Deep Learning in Music Generation and Assisted Music Composition. (2020) - DuBreuil, Alexandre
No abstract available